Increased Toll-Like Receptors Activity and TLR Ligands in Patients with Autoimmune Thyroid Diseases - Peng, Shiqiao; Li, Chenyan; Wang, Xinyi; Liu, Xin; Han, Cheng; Jin, Ting; Liu, Shanshan; Zhang, Xiaowen; Zhang, Hanyi; He, Xue; Xie, Xiaochen; Yu, Xiaohui; et al. (Frontiers in Immunology, 2016)
Abstract Objective: Autoimmune thyroid disease is an organ-specific disorder due to the interplay between environmental and genetic factors. Toll-like receptors are pattern recognition receptors expressed abundantly on monocytes. There is a paucity of data on TLR expression in autoimmune thyroid disease (AITD). The aim of this study was to examine TLR expression, activation, ligands, and downstream signaling adaptors in PBMCs extracted from untreated autoimmune thyroid disease patients and healthy controls. Method: We isolated peripheral blood mononuclear cells (PBMC) of 30 healthy controls, 36 patients with untreated Hashimoto’s thyroiditis (HT), and 30 patients with newly onset Graves’ disease (GD). TLR mRNA, protein expression, TLR ligands, and TLR adaptor molecules were measured using real-time PCR, Western blot, flow cytometry, and enzyme-linked immunoassay (ELISA). PBMC was simulated with TLR agonists. The effects of TLR agonists on the viability of human PBMC were evaluated using the MTT assay. The supernatants of cell cultures were measured for the pro-inflammatory cytokines, IL-6, TNF-α and IL-10 by ELISA. Results: TLR2, TLR3, TLR9, and TLR10 mRNA were significantly increased in AITD patients compared with controls. TLR2, TLR3, TLR9, HMGB1, and RAGE expression on monocytes was higher in patients than control at baseline and TLR agonists stimulation. The release of TNF-a and IL-6 was significantly increased in PBMCs from AITD patients with TLR agonists, while IL-10 was significantly decreased. Downstream targets of TLR, myeloid differentiation factor 88 (MyD88), myeloid toll/interleukin (IL)-1 receptor (TIR)-domain containing adaptor-inducing interferon-β (TRIF) were significantly elevated in AITD patients. Levels of TLR2 ligands, HMGB1 and HSP60 were significantly elevated in AITD patients compared with those in controls and positively correlated with TgAb and TPOAb, while sRAGE concentration was significantly decreased in AITD patients. Conclusion: In conclusion, this work is the first to show that TLR2, TLR3, and TLR9 expression and activation are elevated in the PBMCs of patients with AITD and TLRs may participate in the pathogenesis of AITD.